OP69 Initiatives To Improve The Timeliness Of Cancer Diagnosis. (2019) - Pollock, Michelle; Craig, Rodger; Chojecki, Dagmara; Guo, Bing
Abstract : Introduction: Conventional wisdom suggests that accelerating the speed of cancer diagnosis should improve health outcomes. However, cancer diagnosis requires complex coordination and effective communication between care providers working across many areas of the healthcare system. Since 2000, several nations and jurisdictions have aimed to improve timeliness of cancer diagnosis by integrating and coordinating cancer diagnostic services for patients. The objective of this study was to describe the impact of these existing initiatives. Methods: We conducted an environmental scan consisting of a literature review (published academic and grey literature) and key informant consultations (online surveys and telephone interviews with experts who have knowledge of existing initiatives). We searched for initiatives in the United Kingdom, the Nordic countries, Canada, Australia, and New Zealand. For each initiative, we extracted data on their development and implementation, structure and functioning, intended outcomes and effectiveness, costs and cost savings, and enablers and barriers. Results: Eighty-nine relevant documents and 20 key informants contributed to this study. We identified 21 relevant initiatives, including seven national initiatives targeting multiple types of cancer. The literature review found that most initiatives accelerated the diagnostic phase of cancer care by several days or weeks. These wait time reductions were often associated with improved patient experience, but not less advanced cancer stage or increased long-term survival. Insights from key informants improved our understanding of the costs, enablers, and barriers associated with program implementation and maintenance. Conclusions: These results can be used as a first step to inform the development, evaluation, and improvement of international cancer diagnostic pathways. Stakeholders wishing to accelerate cancer diagnosis should consider the feasibility of achieving their intended program outcomes based on the existing research evidence, desired type of initiative, and jurisdiction's unique contextual factors.